Superhydrophilic poly(l-lactic acid) electrospun membranes for biomedical applications obtained by argon and oxygen plasma treatment - Correia, D. M. (2016)
Poly(l-lactic acid), PLLA, electrospun membranes and films were plasma treated at different times and power with argon (Ar) and oxygen (O2), independently, in order to modify the hydrophobic nature of the PLLA membranes. Both Ar and O2 plasma treatments promote an increase in fiber average size of the electrospun membranes from 830 ± 282 nm to 866 ± 361 and 1179 ± 397 nm, respectively, for the maximum exposure time (970 s) and power (100 W). No influence of plasma treatment was detected in the physicalchemical characteristics of PLLA, such as chemical structure, polymer phase or degree of crystallinity. On the other hand, an increase in the roughness of the films was obtained both with argon and oxygen plasma treatments. Surface wettability studies revealed a decrease in the contact angle with increasing plasma treatment time for a given power and with increasing power for a given time in membranes and films and superhydrophilic electrospun fiber membranes were obtained. Results showed that the argon and oxygen plasma treatments can be used to tailor hydrophilicity of PLLA membranes for biomedical applications. MTT assay results indicated that plasma treatments under Ar and O2 do not influence the metabolic activity of MC3T3-E1 pre-osteoblast cells.